CRITICAL VIEW ON PANDEMIC COVID19 EMOTIONAL IMPACT SCALE: SYSTEMATIC REVIEW AND META-ANALYSIS - Azadeh Mousavi (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2022)
As a major virus outbreak in the 21st century, the Coronavirus disease 2019 (Covid-19) pandemic has led to unprecedented hazards to mental health globally. While psychological support is being provided to patients and healthcare workers, the general public's mental health requires signiﬁcant attention as well. This systematic review aims to create reports about all existing scales on the effects of Covid-19  on psychological outcomes. A systematic search was conducted on PubMed, Embase, Medline, Web of Science, Google Scholar, and Scopus from Inception to 2021 following the PRISMA guidelines. A manual search on Sivilica, Irandoc, and SID manually was performed to identify additional relevant studies among Farsi documents. Articles were selected based on the predetermined eligibility criteria. Relatively about 10 articles about the psychological impacts of covid9 were searched and analyzed according to all aspects of the study. A significant aim of this study is to collect all available questionnaires that examine the psychological impact of pandemics diseases in the duration time of 2019 to 2021.